Adding value to core outcome set development using multimethod systematic reviews. (8th January 2020) - Brunton, Ginny; Webbe, James; Oliver, Sandy; Gale, Chris
Abstract : Trials evaluating the same interventions rarely measure or report identical outcomes. This limits the possibility of aggregating effect sizes across studies to generate high‐quality evidence through systematic reviews and meta‐analyses. To address this problem, core outcome sets (COS) establish agreed sets of outcomes to be used in all future trials. When developing COS, potential outcome domains are identified by systematically reviewing the outcomes of trials, and increasingly, through primary qualitative research exploring the experiences of key stakeholders, with relevant outcome domains subsequently determined through transdisciplinary consensus development. However, the primary qualitative component can be time consuming with unclear impact. We aimed to examine the potential added value of a qualitative systematic review alongside a quantitative systematic review of trial outcomes to inform COS development in neonatal care using case analysis methods. We compared the methods and findings of a scoping review of neonatal trial outcomes and a scoping review of qualitative research on parents', patients', and professional caregivers' perspectives of neonatal care. Together, these identified a wider range and greater depth of health and social outcome domains, some unique to each review, which were incorporated into the subsequent Delphi process and informed the final set of core outcome domains. Qualitative scoping reviews of participant perspectives research, used in conjunction with quantitative scoping reviews of trials, could identify more outcome domains for consideration and could provide greater depth of understanding to inform stakeholder group discussion in COS development. This is an innovation in the application of research synthesis methods.